Cytotoxic Steroids From The Stembak of Chisocheton celebicus KOORD - Dewa Gede Katja; Desi Harneti; Tri Mayanti; Nurlelasari Nurlelasari; Rani Maharani; Yoshihito Shiono; Unang Supratman (Syarif Hidayatullah State Islamic University, 2019)
In the course of our continuing search for anticancer compounds from Chisocheton species, three steroids, stigmast-5-en-3β-ol (1), stigmast-5-en-3β-ol-3-O-β-D-glucopyranoside (2) and stigmast-5,22-dien-3β-ol-3-O-β-D-glucopyranoside (3), were obtained from the stembark of Chisocheton celebicus. The structures of compound 1-3 were identified with spectroscopic data including IR, 1D-NMR, 2D-NMR and TOF-MS, as well as by comparing with those spectral data previously. Compounds 1-3, were evaluated for their cytotoxic effects against P-388 murine leukemia cells and displayed the cytotoxicity activity with IC50 values of 12.45 ± 0.050, 52.27 ± 0.031 and 62.52 ± 0.076 µg/mL, respectively.